Intensification in English and Spanish communication - Flores-Ferrán, Nydia (Lexington Books, 2022)
"Intensification in English and Spanish Communication provides a broad account of how speakers and writers escalate their communication with the purpose of persuading their hearers and interlocutors. The author provides examples of the linguistic elements, features, strategies, and devices used by native speakers to amplify their communication"--